Assessment of marine geoid models by ship-borne GNSS profiles - Varbla, Sander; Gruno, Anti; Ellmann, Artu; Märdla, Silja (International Conference “Environmental Engineering”, 2017)
The Baltic Sea Hydrographic Commission (BSHC) is introducing the Baltic Sea Chart Datum 2000 (BSCD2000) as new common height reference system for hydrographic surveying and nautical charts from 2020. The BSCD2000 will be a geodetic height system that uses an equipotential surface (geoid) as zero reference level for height/depth determination. For this an international FAMOS (Finalising Surveys for the Baltic Motorways of the Sea) project has been initiated to improve the gravimetric quasigeoid model that will be needed for the realisation of BSCD2000 over the Baltic Sea. The goal is to improve the accuracy of GNSS-based bathymetric measurements and navigation by computing a new geoid model with 5 cm accuracy over the Baltic Sea. Even though the entire Baltic Sea is included in previous geoid modelling projects such as the NKG2015 and EGG07, the accuracy of contemporary geoid models over marine areas is unknown, presumably being offshore around 15-20 cm. An important part of the FAMOS efforts is conducting new marine gravity observations on board hydrographic surveying ships or as dedicated gravity survey campaigns. These new data are essential to the project as the existing gravimetric data in the Baltic Sea may be not dense and accurate enough for the purpose of 5 cm geoid modelling. However, it is important to evaluate geoid modelling outcome by independent data. On land, geoid models are customarily assessed by using precise leveling and Global Navigation Satellite System points, whereas in offshore such control points cannot be established. Instead, marine geoid models can be assessed by continuous GNSS measurements on board ships. Accordingly, this study presents results of the ship-borne marine gravity and GNSS campaign held by the Estonian Maritime Administration survey vessel Jakob Prei in West-Estonian archipelago in June/July 2016. Emphasis of the study is on principles of using the GNSS-profiles for validation of existing geoid models, post-processing of GNSS raw data, low-pass filtering of the GNSS results. The GNSS-derived heights are corrected to account for the systematic effects induced by ship dynamics and other static or dynamic impacts from tides, atmospheric pressure, or wind stress. It is concluded that the marine GNSS datasets have potential in providing complementary constraints in problematic geoid modelling areas.